Computational fluid dynamic analysis of the effect of inlet valve closing timing on common rail diesel engines fueled with butanol–diesel blends - Lamani, Venkatesh T.; Shivaprasad, K. V.; Roy, Dibyendu; Yadav, Ajay Kumar; Kumar, G. N. (Frontiers in Energy Research, 2024)
The inlet valve closing (IVC) timing plays a crucial role in the engine combustion which impacts engine performance and emission. This study attempts to measure the potential to employ n-butanol (a biofuel) and its blends with the neat diesel in a common rail direct injection (CRDI) engine. The computational fluid dynamics (CFD) simulation is carried out to estimate the performance, combustion, and exhaust emission characteristics of n-butanol-diesel blends (0 to 30% by volume) for variable valve timings. Experimental study is carried out at standard valve timing and blends to validate the CFD model (ESE AVL FIRE). After validation, CFD model is employed to study the effect of variable valve timings for different n-butanol-diesel blends. Extended coherent flame model-3 zone (ECFM-3Z) is implemented to carry out combustion analysis, and K-epsilon (k-ε) model is employed for turbulence modeling. The inlet valve closing (IVC) time is varied (advanced and retarded) from standard conditions and optimized valve timing is obtained. Advancing intake valve closing (IVC) time leads to lower cylinder pressure during compression due to the reduction in trapped mass of air. The BTE is increased by 4.5%, 6% and 8% for Bu10, Bu20 and Bu30 respectively compared to Bu0. Based on BTE, optimum injection timings are obtained at 12º BTDC for Bu0 and 15° BTDC for Bu10, Bu20 and Bu30. NOx emission is increases due to complete combustion. Further carbon monoxide and soot formation decreased with blends and insignificant effect due to IVC timing.